If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3b + -2b = -3 Combine like terms: 3b + -2b = 1b 1b = -3 Solving 1b = -3 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Divide each side by '1'. b = -3 Simplifying b = -3
| 5/3•11/3 | | 1.3x-0.02=1.9x+0.16 | | 12r-8-12(r+2)= | | 4x+10=4x-8 | | 8-3(w+3)=4(2w-14) | | 6x+10=(3x+5)2 | | 2xsquare-7x-15=0 | | -10-2d+15=-12-3d | | 4(y+3)=5(y+3) | | 0.2x+0.7=1.2-0.3x | | 56/x=22 | | 6+2x+10=-60 | | f(x)=2x+5givenf(a+5) | | X/2-x/3=11 | | 2x^2+100x-658469=0 | | (9m-3n)(6m+11n)= | | 22x^2-11xy=0 | | 20v+16=-19+7v+18v | | 6x+2(3x-1)= | | 3sinx-5cosx=2 | | 20v+16=19+7v+18v | | 7m+4=7 | | 9n-13=11+19n-12n | | x+1=4-2x | | 2x^2+100x+1687=0 | | 7x-2x-15=9-15 | | 9=3-3x | | 6(2-4x)=-7 | | -30+10=-2x | | 3+9q=7+8q | | -14u-20=-5u+16 | | -3/11x=2 |